2021
DOI: 10.1155/2021/8881191
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic Rift Valley Fever Outbreaks in Humans and Animals in Uganda, October 2017–January 2018

Abstract: Introduction. Rift Valley fever (RVF) is a mosquito-borne viral zoonosis. The Uganda Ministry of Health received alerts of suspected viral haemorrhagic fever in humans from Kiruhura, Buikwe, Kiboga, and Mityana districts. Laboratory results from Uganda Virus Research Institute indicated that human cases were positive for Rift Valley fever virus (RVFV) by polymerase chain reaction. We investigated to determine the scope of outbreaks, identify exposure factors, and recommend evidence-based control and prevention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
2
11
1
Order By: Relevance
“…These results could indicate that RVFV circulates sub-clinically in our livestock sheep. The high seroprevalence (66.67%) found in this study is comparable to the 75% reported in Senegal [ 29 ], 55% from Mauritania [ 35 ], and 45% from Uganda [ 34 ]. Our prevalence is higher than that reported in Senegal (14.3%) [ 8 ], Mauritania (3.8%) [ 36 ], the Central African Republic (12.9%) [ 37 ], and Uganda (4%) [ 38 ], which could be explained by the long exposure time (11 months) of the sentinel sheep in natural settings.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These results could indicate that RVFV circulates sub-clinically in our livestock sheep. The high seroprevalence (66.67%) found in this study is comparable to the 75% reported in Senegal [ 29 ], 55% from Mauritania [ 35 ], and 45% from Uganda [ 34 ]. Our prevalence is higher than that reported in Senegal (14.3%) [ 8 ], Mauritania (3.8%) [ 36 ], the Central African Republic (12.9%) [ 37 ], and Uganda (4%) [ 38 ], which could be explained by the long exposure time (11 months) of the sentinel sheep in natural settings.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, Agnam is located in the Matam region, one of the main paths of human transport of livestock into Senegal, Mauritania, and Mali [ 32 ]. Interestingly, previous studies show that transboundary livestock trade between countries has been related to the Comoros island RVFV outbreak [ 33 ] and the reemergence of RVFV in Somalia [ 34 ]. Indeed, epizootics (amplification of the virus in an animal population such as livestock animals) acting as a vector have usually preceded human RVFV epidemics [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…We report 7 RVFV infections, 4 recent infections (positive by IgM testing, rRT-PCR, or both) and 3 past infections (IgG positive only), identified May-June 2021 in Kiruhura District, Uganda. The western region of Uganda, including Kiruhura District, is within the cattle corridor (Figure 1) and at high risk for RVF and Crimean-Congo hemorrhagic fever because of large livestock populations (9,10). The RVF case-patient who died was a young, previously healthy resident of a farming community with a history of contact with cattle and drinking raw milk from a herd with reported manifestations compatible with RVF.…”
Section: Discussionmentioning
confidence: 99%
“…Coordinated effort between the public and animal health administrations in line with the One Health approach to control the spread sporadic diseases like RVF is suggested. It could be achieved by antibodies and RT‐PCR based surveillance programmes to screen and diagnose RVF in humans and domesticated animals 17–19 . Antibodies against viral nucleo‐ and glycoproteins could facilitate the diagnosis 20 .…”
Section: Rvfv Diagnosis and Complicationsmentioning
confidence: 99%